2016
DOI: 10.3847/0004-637x/818/2/195
|View full text |Cite
|
Sign up to set email alerts
|

An HST Proper-Motion Study of the Large-Scale Jet of 3c273

Abstract: The radio galaxy 3C 273 hosts one of the nearest and best-studied powerful quasar jets. Having been imaged repeatedly by the Hubble Space Telescope (HST) over the past twenty years, it was chosen for an HST program to measure proper motions in the kiloparsec-scale resolved jets of nearby radio-loud active galaxies. The jet in 3C 273 is highly relativistic on sub-parsec scales, with apparent proper motions up to 15c observed by very long baseline interferometry. In contrast, we find that the kiloparsec-scale kn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 58 publications
(86 reference statements)
4
25
0
Order By: Relevance
“…There is another factor which likely makes these jets outliers in addition to the orientation angle. As noted previously, population-based evidence as well as individual limits on δ from both proper motions (in 3C 273; Meyer et al 2016) and deep Fermi/LAT limits on the IC/CMB emission imply most large-scale jets are only mildly relativistic. Here we require high values of the Lorentz factor on extremely large scales -assuming the maximum angle, the jets in OJ 287 and PKS 1510−089 deproject to lengths of at least 600 and 800 kpc.…”
Section: Resultssupporting
confidence: 58%
“…There is another factor which likely makes these jets outliers in addition to the orientation angle. As noted previously, population-based evidence as well as individual limits on δ from both proper motions (in 3C 273; Meyer et al 2016) and deep Fermi/LAT limits on the IC/CMB emission imply most large-scale jets are only mildly relativistic. Here we require high values of the Lorentz factor on extremely large scales -assuming the maximum angle, the jets in OJ 287 and PKS 1510−089 deproject to lengths of at least 600 and 800 kpc.…”
Section: Resultssupporting
confidence: 58%
“…A remarkable point is that the vertical distribution Dθ1 systematically yields a larger inclination angle of ∼ 30 • , whereas the distribution Dθ2 yields an inclination angle of ∼ 6 • . The latter value is consistent with the inclination 3.8 • -15 • of the jet in 3C 273 measured by radio observations (e.g., Lobanov & Zensus 2001;Savolainen et al 2006;Meyer et al 2016;Jorstad et al 2017). The main reason for such a dichotomy is as follows (see also discussions in Grier et al 2017 andLi et al 2018).…”
Section: Overviewsupporting
confidence: 87%
“…First, 3C 273 displays a prominent radio jet (e.g., Courvoisier 1998). The viewing inclination measured through superluminal motion ranges from 3.8 • to ∼15 • (Lobanov & Zensus 2001;Savolainen et al 2006;Meyer et al 2016;Jorstad et al 2017). This provides a useful constraint if assuming an alignment between the rotation axis of the BLR and the jet.…”
Section: Model Selectionmentioning
confidence: 99%
“…That was seen to be inconsistent with the observed properties of that source. While some of these sources are known to be highly beamed on parsec scales-for example, 3C 273 has apparent superluminal speeds as high as 15c [39]-it has always been assumed that jets must decelerate on kpc scales (e.g., [42,47], and moreover, in the case of 3C 273, a study of proper motions on the kiloparsec scales found an upper limit of 2c [40], highly inconsistent with the requirement of the IC-CMB model [36,40]. Individually, in fact, those models show that these knots are inconsistent with IC-CMB emission by large factors-anywhere from 2σ for the faintest components to over 20 σ for the brightest components.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…More recently, analysis of Fermi observations of multiple other quasars [35][36][37][38] including the jets of 3C 273 and PKS 0637-752, also proved to be inconsistent with the IC-CMB emission process being dominant in the X-rays, as the same electron population would inverse-Comptonize optical synchrotron photons into the GeV gamma-ray band, thus requiring a similarly high beaming factor that overpredicts the observed low-state emissions detected by Fermi by orders of magnitude. While 3C 273 has components with varying apparent speeds, as high as 15c (see, e.g., [39]), those components are on parsec scales, while the observed X-ray emission is on projected scales of tens of kiloparsecs, where HST observations have failed to find any evidence of superluminal motions [40]. A similar problem exists for PKS 0637-752, where VLBI observations [41] show similarly fast, superluminal components.…”
Section: Introductionmentioning
confidence: 93%